1982
DOI: 10.1128/aac.22.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the cephalosporin SM-1652 in mice, rats, rabbits, dogs, and rhesus monkeys

Abstract: The pharmacokinetics of SM-1652 were studied in mice, rats, rabbits, dogs, and rhesus monkeys. The plasma half-lives of SM-1652, administered intravenously at a dose of 20 mg/kg, were 11.0 min in mice, 26.0 min in rats, 65.8 min in rabbits, 72.6 min in dogs, and 150.9 min in monkeys. The 24-h urinary excretion of SM-1652 was 30 to 35% of the dose in mice and rats, 70 to 75% in rabbits and dogs, and 45% in monkeys. Biliary excretion of the antibiotic over a 24-h period was 60 and 19% in rats and rabbits, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
20
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 7 publications
5
20
0
1
Order By: Relevance
“…In the present study, the percentage of the dose of CPM excreted into the bile obtained in 20-week-old healthy SDRs (58%) was consistent with the value (60%) obtained in healthy SDRs reported previously (18). We found marked decreases in the CL bile of CPM in EHBRs; the CL bile values of CPM dropped in 10-and 20-week-old EHBRs to 1/7 and 1/15, respectively, of that in healthy SDRs, although the differences between the two EHBR groups failed to reach the 5% level of statistical significance.…”
Section: It Is Known That the Biliary Excretion Of Organic Anions Is supporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the percentage of the dose of CPM excreted into the bile obtained in 20-week-old healthy SDRs (58%) was consistent with the value (60%) obtained in healthy SDRs reported previously (18). We found marked decreases in the CL bile of CPM in EHBRs; the CL bile values of CPM dropped in 10-and 20-week-old EHBRs to 1/7 and 1/15, respectively, of that in healthy SDRs, although the differences between the two EHBR groups failed to reach the 5% level of statistical significance.…”
Section: It Is Known That the Biliary Excretion Of Organic Anions Is supporting
confidence: 93%
“…On the other hand, nonbiliary and nonrenal clearances for CPM did not change among the three groups and contributed little to the elimination of CPM from the body (6 to 12% of CL sys ). It has been reported that CPM is almost completely recovered in the urine and bile in the unchanged form (Ͼ90%) and that the amount of its metabolite that is recovered is negligible (18). The results from the present study also indicate that the increased urinary excretion of CPM in EHBRs compensates for a reduction in the biliary excretion ability, although this compensation is not complete.…”
Section: It Is Known That the Biliary Excretion Of Organic Anions Is supporting
confidence: 66%
See 2 more Smart Citations
“…It is highly protein bound (96.3% at 100 pg/ml) and has a reported half-life of 4.4 h in volunteers with normal renal function (6,7). High and prolonged concentrations in blood are achieved after intravenous infusion.…”
mentioning
confidence: 99%